A review of decreased sound tolerance in autism: Definitions, phenomenology, and potential mechanisms. (February 2021) - Williams, Zachary J.; He, Jason L.; Cascio, Carissa J.; Woynaroski, Tiffany G.
Highlights: Decreased sound tolerance (DST) is a common and disabling feature of autism. DST in autism is a combination of hyperacusis, misophonia, and phonophobia. Hyperacusis is thought to result from excessive gain in the central auditory system. Misophonia may be caused by the attribution of excess salience to certain sounds. Phonophobia is a specific phobia of sound maintained by impaired fear extinction. Abstract: Atypical behavioral responses to environmental sounds are common in autistic children and adults, with 50–70 % of this population exhibiting decreased sound tolerance (DST) at some point in their lives. This symptom is a source of significant distress and impairment across the lifespan, contributing to anxiety, challenging behaviors, reduced community participation, and school/workplace difficulties. However, relatively little is known about its phenomenology or neurocognitive underpinnings. The present article synthesizes a large body of literature on the phenomenology and pathophysiology of DST-related conditions to generate a comprehensive theoretical account of DST in autism. Notably, we argue against conceptualizing DST as a unified construct, suggesting that it be separated into three phenomenologically distinct conditions: hyperacusis (the perception of everyday sounds as excessively loud or painful), misophonia (an acquired aversive reaction to specific sounds), and phonophobia (a specific phobia of sound), each responsible for a portion of observed DST behaviors. We further elaborate our framework by proposing preliminary neurocognitive models of hyperacusis, misophonia, and phonophobia that incorporate neurophysiologic findings from studies of autism.